Flower visitors to the cloudberry (Rubus chamaemorus L.) in northern Fennoscandia - Hippa, Heikki; Koponen, Seppo; Osmonen, Olli. (1981)
Summary: Insects visiting cloudberry flowers were studied in three areas north of the Arctic Circle: Forests and Fell Lapland in Finland, and Finnmark in Norway...
kart.
Lap22
Keywords: 1970-luku; 1970-talet; hyönteistiede; pölyttäjät; luonnonmarjat; pölytys; lakka (vatukat); entomologi; pollinerare; vilda bär; pollinering; hjortron; hilla; Lappi; Kevo (Utsjoki); Rovaniemi; Norja; Lappland; Kevo (Utsjoki); Rovaniemi; Norge; Olkkajärvi; Finnmark